Proses Penalaran Kuantitatif Menggunakan Kerangka Referensi Siswa Ditinjau Dari Gender - Siolimbona, Dedi Rahman; Budiarto, Mega Teguh; Sofro, A'yunin (Universitas Dr. Soetomo, 2021)
Abstract The results of previous studies showed that the ratio of the differences in the level of quantitative reasoning abilities between male students and female students was quite significant. While the frame of reference refers to a series of mental actions through which individuals can regulate the processes and products of quantitative reasoning. Therefore, there are two main objectives of this study, namely to show whether or not there are differences in quantitative reasoning products using a frame of reference between male and female students, then to describe the process of quantitative reasoning using a frame of reference between male and female students. Using Sequential Mixed Methods, this study examined 58 students of class VIII junior high school. The research was conducted in two phases, namely the quantitative phase which included statistical data analysis using the Mann Withney Test to determine whether there were differences in the product of quantitative reasoning using the frame of reference for male and female students. Then the qualitative phase includes a description of the quantitative reasoning process using a frame of reference for male and female students. The results of the study stated that there were differences in the product of quantitative reasoning between male and female students. This is indicated by the results of statistical tests in the quantitative phase, while the qualitative phase found that male students were able to analyze the formulas that were determined according to the results of their own interpretation of the information provided implicitly or explicitly in the questions compared to female students. Keywords: Quantitative Reasoning, Frame of Reference, Gender Abstrak Hasil penelitian sebelumnya menunjukan rasio perbedaan tingkat kemampuan penalaran kuantitatif antara siswa laki-laki dan siswa perempuan yang cukup signifikan. Sedang kerangka referensi merujuk pada serangkaian tindakan mental yang melaluinya individu dapat mengatur proses dan produk dari penalaran kuantitatif. Oleh karenanya, ada dua tujuan utama dari penelitian ini, yaitu menunjukkan ada atau tidak-nya perbedaan produk penalaran kuantitatif menggunakan kerangka referensi antara siswa laki-laki dan perempuan, selanjutnya mendeskripsikan proses penalaran kuantitatif menggunakan kerangka referensi antara siswa laki-laki dan perempuan. Menggunakan Sequential Mixed Methods penelitian ini mengkaji 58 orang siswa kelas VIII SMP. Penelitian dilakukan dengan dua fase, yaitu fase kuantitatif meliputi analisis data statistik menggunakan uji Mann Withney Test untuk mengetahui adakah perbedaan produk penalaran kuantitatif menggunakan kerangka referensi siswa laki-laki dan perempuan. selanjutnya fase kualitatif meliputi, deskripsi proses penalaran kuantitatif menggunakan kerangka referensi siswa laki-laki dan perempuan. Hasil penelitian menyatakan ada perbedaan produk penalaran kuantitatif antara siswa laki-laki dan perempuan. Hal ini ditunjukkan oleh hasil uji statistik pada fase kuantitatif, sedangkan fase kualitatif menemukan bahwa siswa laki-laki lebih dapat menganalisis rumus/formula yang ditentukan menurut hasil interpretasinya sendiri terhadap informasi yang diberikan secara implisit maupun eksplisit dalam soal disbanding siswa perempuan. Kata Kunci: Penalaran Kuantitatif, Kerangka Referensi, Gender.